2016
DOI: 10.25215/0303.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Therapy and Mindfulness Training in the Treatment of Adults Who Stutter

Abstract: Introduction: Stuttering is a developmental speech disorder with multiple etiological factors. Cognitive behavior therapy (CBT) has shown effectiveness in reducing anxiety symptoms and dysfluent speech in adults who stutter (AWS). So we planned to study the comparative efficacy of CBT and CBT combined with mindfulness training (MT) in AWS. Aim: The aim of this preliminary study was to examine and compare the efficacy of CBT and CBT combined with MT in reducing anxiety symptoms, and dysfluent speech and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The importance of targeting the psychosocial implications of stuttering is well evidenced by the increase in effective psychological interventions for stuttering being identified in the research arena and used clinically with the stuttering population. These include cognitive behavioural therapy (CBT) and mindfulness-based interventions such as acceptance and commitment therapy (ACT) (Beilby et al, 2012;Cheasman, 2013;Helgadóttir et al, 2014;Gupta et al, 2016;Tichenor et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of targeting the psychosocial implications of stuttering is well evidenced by the increase in effective psychological interventions for stuttering being identified in the research arena and used clinically with the stuttering population. These include cognitive behavioural therapy (CBT) and mindfulness-based interventions such as acceptance and commitment therapy (ACT) (Beilby et al, 2012;Cheasman, 2013;Helgadóttir et al, 2014;Gupta et al, 2016;Tichenor et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the automatic thought of “I am stuttering, and that is bad” can instead become, simply, “I am stuttering.” Detaching or defusing the emotion from the thought (Anderson & Levy, 2009; Jha et al, 2010; Wells & Papageorgiou, 2004) can help reduce the impact of negative automatic thoughts. There is growing research that mindfulness-based therapies are effective at decreasing the burden of living with stuttering (Beilby et al, 2012; Cheasman, 2013; Gupta, 2015; Gupta et al, 2016; Palasik & Hannan, 2013). A clinician whose therapy incorporates mindfulness-based techniques, such as staying in a moment and practicing nonjudgment, can help clients decrease both the frequency and the severity of RNT (see Tichenor & Yaruss, 2020a, for discussion).…”
Section: Implications For Stuttering Assessment and Treatmentmentioning
confidence: 99%
“…Mindfulness and desensitization are just some of the tools that SLPs can use to help speakers reduce negative reactions to stuttering. Cognitive therapy approaches, such as Cognitive–Behavioral Therapy (CBT) and Acceptance and Commitment Therapy (ACT; Beilby et al, 2012; Beilby & Byrnes, 2012; Blood, 1995; Cheasman, 2013; Emerick, 1988; Gupta et al, 2016; Helgadóttir et al, 2014; Kelman & Wheeler, 2015; Menzies et al, 2008, 2009; Palasik & Hannan, 2013), have also been shown to be valuable for decreasing negative personal reactions to stuttering. For example, CBT can be used to decrease the frequency or severity of negative thoughts, feelings, and behaviors related to stuttering.…”
Section: Implications For Stuttering Assessment and Treatmentmentioning
confidence: 99%
“…In more recent times, however, efficacy evidence for a range of psychological interventions targeting unhelpful personal reactions and the reduction of the adverse impact of living with stuttering has increased. Research on cognitive‐based interventions such as cognitive behavioural therapy (CBT) and more recently mindfulness‐based interventions such as acceptance and commitment therapy (ACT) have demonstrated efficacy in decreasing anxiety, increasing positive reactions to stuttering and reducing the adverse impact of stuttering for children and adults (Beilby et al., 2012; Cheasman, 2013; Gupta et al., 2016; Helgadóttir et al., 2014; Kelman & Wheeler, 2015; Menzies et al., 2008; St Clare et al., 2009; Tichenor et al., 2022). Despite the increased implementation of such therapies within the field of stuttering, there is little, if any, discussion on their philosophical origins, which date back to ancient Greek and Roman civilisations.…”
Section: Introductionmentioning
confidence: 99%